Diagnostic value of fecal B cell activating factor in patients with abdominal discomfort. (5th August 2019) - Xie, C.; Quan, R.; Wang, L.; Chen, C.; Yan, W.; Fu, Y.
Summary: Fecal calprotectin has successfully been widely recommended as a sensitive biomarker of inflammatory bowel diseases (IBD). Recently, we have identified an excellent new fecal biomarker, B cell activating factor (BAFF), as being as effective as fecal calprotectin for diagnosing intestinal inflammation. In this study, a total of 230 patients with abdominal discomfort were prospectively enrolled and fecal samples were collected within 24 h before the endoscopic examinations. We show that fecal BAFF levels were significantly higher in patients with ulcerative colitis (median = 1549 pg/g, P < 0·0001), Crohn's disease (median = 735 pg/g, P < 0·0001), gastric cancer (median = 267 pg/g, P < 0·0001) and colorectal cancer (median = 533 pg/g, P < 0·0001) than those in healthy groups (median = 61 pg/g), while the values of which in patients with gastric polyps, colorectal polyps, esophagitis/gastritis/duodenitis and peptic ulcer were in the range of healthy individuals ( P > 0·05). An optimal cut‐off value at 219·5 pg/g of fecal BAFF produced sensitivity, specificity, positive predictive and negative predictive values of 85, 91, 84 and 92%, respectively, for IBD or carcinoma. Our results therefore indicate a potential role for fecal BAFF as a sensitive screening parameter for IBD and gastrointestinal carcinoma, as well a useful tool to select patients with abdominal discomfort for further endoscopic examinations. Abstract : A new fecal biomarker, B‐cell activating factor, was investigated among patients with abdominal discomfort in this study. Fecal BAFF values were conducted in various gastrointestinal diseases and its diagnostic values were calculated, suggesting a potential role for fecal BAFF to be a sensitive screening parameter for inflammatory bowel diseases and gastrointestinal carcinoma.